Farmers’ perceptions towards agroforestry systems in North and South Kordofanstates, Sudan - Fadl, Kamal Eldin Mohammed; Mahmoud, Salah E; Hamad, Zainab M (International Journal of Environment, 2015)
This study was conducted during 2010 and 2011 in North and South Kordofan States with objectives of to identify and assess the most important agroforestry systems, to characterize major tree species in different agroforestry system, to prioritize major constraints on agroforestry systems in the region, and to study the current status of gum Arabic trees and their contribution on farmers livelihood. Data were collected through community meeting, individual interviews and direct field observation. The common agroforestry systems in the region are scatter trees on farm land, followed by wind breaks and boundary planting. The important trees in the study area are Acacia senegal83%, followed by Fadherbia albida 46%, Ziziphus spina- christia43% and Balanites aegyptiaca 41%. The most important field crops that cultivated in agroforestry system are groundnuts, millet, sorghum, sesame and roselle. The environmental benefits of trees in farm which was identified by the respondents include protection of farm against wind erosion, improvement of the soil properties, improvement of the micro-climate and providing a source for income which was indicated by the majority of respondents. Across all sites 93% of respondents showed that gum Arabic have a significant contribution to their family income. The study recommended that a multi-purpose tree species such as Acacia senegal should be maintained for amelioration of soils fertility and increase crop productivity in the fragile ecosystems such as that of the study sites. DOI: http://dx.doi.org/10.3126/ije.v4i2.12624 International Journal of Environment Vol.4(2) 2015: 53-67